A method for the extraction and partial isolation of the glycosides from the leaves of Cananga odorata - Polintan, Paulino (Quezon City: Department of Pharmaceutical Chemistry, College of Pharmacy, University of the Philippines, 1983.)
50 grams of the air-dried leaves of Cananga odorata were macerated with 90% alcohol as solvent. This macerate was concentrated to a syrupy consistency by distillation under reduced pressure then evaporated spontaneously to obtain a greenish mass. This mass is extracted with successive portions of acetone to remove the green color. This brown residue left is then isolated from the insoluble solids and impurities by column chromatography. The methanol eluates are combined and evaporated to dryness on a water bath to yield slightly greenish solids of the glycosides.
The extraction and partial isolation of the glycoside were made possible utilizing thin layer chromatography which involved both uni-dimensional and two-dimensional tests and also by a column chromatographic method. The corresponding product and intermediates were checked for the presence of the glycoside by chemical methods such as through Fehling?s test, lead acetate test, and lead subacetate tests; and by the use of instruments as infra-red spectroscopy.
There is no intention of identifying the structure of the glycoside extracted. Only the method of extraction and partial isolation was performed although a number of the properties of the glycoside were also studied.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, October 1983.
Keywords: Glycosides; Ilang-ilang.